2023
DOI: 10.1186/s10020-023-00692-9
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine exacerbates diabetic nephropathy through upregulation of Grem1 expression

Abstract: Background Diabetic nephropathy (DN) is a major complication of diabetes mellitus. Clinical reports indicate that smoking is a significant risk factor for chronic kidney disease, and the tobacco epidemic exacerbates kidney damage in patients with DN. However, the underlying molecular mechanisms remain unclear. Method In the present study, we used a diabetic mouse model to investigate the molecular mechanisms for nicotine-exacerbated DN. Twelve-week… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(79 reference statements)
0
1
0
Order By: Relevance
“… 41 Moreover, our recent study showed that the oxidative stress response in DN was significantly enhanced and that the TGF-β signaling pathway was activated considerably, with significantly increased levels of Smad2/3 and Smad1/5/8 proteins phosphorylation. 42 This may enhance renal fibrosis and further compromise renal function in the diabetic milieu.…”
Section: Introductionmentioning
confidence: 99%
“… 41 Moreover, our recent study showed that the oxidative stress response in DN was significantly enhanced and that the TGF-β signaling pathway was activated considerably, with significantly increased levels of Smad2/3 and Smad1/5/8 proteins phosphorylation. 42 This may enhance renal fibrosis and further compromise renal function in the diabetic milieu.…”
Section: Introductionmentioning
confidence: 99%